Factors that contribute the acceptance of Gold Dinar in Kelantan / Siti Nur Ain Ismail - Ismail, Siti Nur Ain (Bachelor of Business Administration (Hons) Finance, 2013)
The purpose of this study is to determine the relationship between medium of exchange, economic, social, and political with public acceptance of Gold Dinar in Kelantan. The other objective is to determine which of independent variables that contributes the acceptance of the gold dinar in Kelantan. The data was gathered via questionnaires and a total of respondents are 200 that participated in answering the questions. The data was processed using IBM SPSS Version 20. Several techniques were used including frequency analysis, reliability analysis, descriptive analysis, correlation of coefficient, and regression analysis. From this research, it shows that all the factors have their own relationship towards public acceptance